2013
DOI: 10.1093/rpd/nct099
|View full text |Cite
|
Sign up to set email alerts
|

Determination of radon concentration levels in well water in Konya, Turkey

Abstract: Radon ((222)Rn) measurements were undertaken in 16 samples of well water representing different depths and different types of aquifers found at the city centre of Konya, Central Turkey. The radon activity concentrations of the well water samples collected in the spring and summer seasons of 2012 were measured by using the radon gas analyser (AlphaGUARD PQ 2000PRO). The radon concentrations for spring and summer seasons are 2.29 ± 0.17 to 27.25 ± 1.07 and 1.44 ± 0.18 to 27.45 ± 1.25 Bq l(-1), respectively. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 15 publications
1
4
0
3
Order By: Relevance
“…Erdogan et al found a slight positive correlation in their study of wells in Turkey. 21 Alkalinity and turbidity, however, showed a clearer trend and positive correlation. Other studies with physico-chemical parameters did not indicate any correlations.…”
Section: Discussionmentioning
confidence: 92%
“…Erdogan et al found a slight positive correlation in their study of wells in Turkey. 21 Alkalinity and turbidity, however, showed a clearer trend and positive correlation. Other studies with physico-chemical parameters did not indicate any correlations.…”
Section: Discussionmentioning
confidence: 92%
“…This may be due to the fact that fractures with higher permeability/porosity can increase bedrock surface area in fault zones, allowing 222 Rn to dissolve from the bedrock into groundwater through active water-rock interactions. Previous studies have reported that fractures can enhance emanation surfaces, allowing 222 Rn to escape from rocks via α-recoil [32,33]. The relatively lower 222 Rn concentration in groundwater close to Faults B and C may be due to the different lithology (gneiss) of those well locations.…”
Section: Spatial Distributions Of 222 Rn and Umentioning
confidence: 95%
“…Данный вопрос требует отдельного целенаправленного исследования, так как мнения специалистов о характере подобной зависимости расходятся. Это позволяет на данном этапе работ в качестве основной причины выяв-ленной закономерности рассматривать изменение температуры воды, тем более что для некоторых регионов обратная связь между параметрами Q и T установлена достаточно определенно [Erdogan et al, 2013;Schubert et al, 2012]. Поскольку радиоак-тивный газ лучше растворяется в водах с более низкой температурой, повышение радиоактивно-сти наблюдается у побережья Байкала, где под влиянием озера происходит охлаждение подзем-ных вод.…”
Section: структурный фактор контроля подземных вод с повышенным содерunclassified